Influence of Process Parameters on Ceroxide Formation in Low-Carbon Steels - Vaucheret, Alexis; Nicoli, Cécile; Carton, Jean-François; Jacquet, Philippe (Journal of Casting & Materials Engineering, 2018)
Ceroxides are surface defects caused by a mold-metal reaction during the casting process of steels. This type of defect may affect a large area, but it is located only on the skin of the parts. It does not affect the core of the parts nor its mechanical properties. Nevertheless, ceroxides induce a lack of material on the surface, forming a kind of crater and needing complementary surfacing.The defect is also composed by several non-metallic inclusions containing Al, Mg, Si and O. An EDX analysis by mapping show these elements involved in the mold-metal reaction. The presence of these oxides could confirm the hypothesis of the deoxidizer reoxidation found in the bibliography.To better understand the specific conditions of ceroxide formation, the first step was to find of way to generate systematically this defect at each casting. Two patterns with different filling rate were designed, simulated on Quikcast and tested. The pattern with turbulent filling rate allowed the formation of ceroxide at each casting and so was used during this study. This result shows that the filling rate of the mold could be considered as a first order parameter in ceroxide formation. Then, a specific experimental set up was designed to characterize this defect. The analysis of the defect was done for sizing it: surface and depth.Finally, some key parameters on defect formation were determined like the nature of deoxidizer or the amount of oxygen in the mould. Some laboratory tests were lead to show the influence of these parameters by characterization of the casted parts in comparison with a reference sample. This study allowed us to find process parameters responsive of  ceroxide formation and to propose some way of improvement to reduce the size and the occurrence of ceroxides.